Lipopolysaccharide O-antigen molecular and supramolecular modifications of plant root microbiota are pivotal for host recognition. (1st February 2022) - Vanacore, Adele; Vitiello, Giuseppe; Wanke, Alan; Cavasso, Domenico; Clifton, Luke A.; Mahdi, Lisa; Campanero-Rhodes, María Asunción; Solís, Dolores; Wuhrer, Manfred; Nicolardi, Simone; Molinaro, Antonio; Marchetti, Roberta; et al.
Abstract: Lipopolysaccharides, the major outer membrane components of Gram-negative bacteria, are crucial actors of the host-microbial dialogue. They can contribute to the establishment of either symbiosis or bacterial virulence, depending on the bacterial lifestyle. Plant microbiota shows great complexity, promotes plant health and growth and assures protection from pathogens. How plants perceive LPS from plant-associated bacteria and discriminate between beneficial and pathogenic microbes is an open and urgent question. Here, we report on the structure, conformation, membrane properties and immune recognition of LPS isolated from the Arabidopsis thaliana root microbiota member Herbaspirillum sp. Root189. The LPS consists of an O -methylated and variously acetylated D-rhamnose containing polysaccharide with a rather hydrophobic surface. Plant immunology studies in A. thaliana demonstrate that the native acetylated O-antigen shields the LPS from immune recognition whereas the O -deacylated one does not. These findings highlight the role of Herbaspirillum LPS within plant-microbial crosstalk, and how O-antigen modifications influence membrane properties and modulate LPS host recognition. Graphical abstract: Unlabelled Image